(untitled) (CIPEEX, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) are significant respiratory conditions with a global impact on public health. COPD leads to chronic inflammation and respiratory difficulties, while OSA, characterized by episodes of apnea and hypopnea, affects sleep quality. Objective: To review the literature in order to understand the severity and prevalence of OSA in COPD patients undergoing pulmonary rehabilitation (PR). Methodology: Three clinical trials were extracted from the PubMed database, published between 2015 and 2024. The Health Sciences Descriptors (DeCS) used for the search were: "chronic obstructive pulmonary disease," "obstructive sleep apnea," "rehabilitation," "prevalence," and "severity," in English and Portuguese, with the boolean operator "AND." The inclusion criteria were publications in Portuguese and English, original studies, and open access. Results: OSA is prevalent in patients with COPD, with variations in the severity of respiratory disorders, and it was found that RP showed benefits in quality of life and control of overlap syndrome; however, factors such as body mass index and comorbidities also influence the severity of COPD. Conclusion: The association between COPD and OSA is common and negatively affects the quality of life of patients, and RP offers significant improvements; however, more studies are needed to strengthen the evidence and seek scientific consensus.